APPLICATION OF PEDAGOGICAL PRINCIPLES IN THE DESIGN OF ACADEMIC INFORMATION WEBSITE FKIP UNTAN - Firmansyah, Andang; Yansa, Hemri; Saptahadi, Dwija (International Journal of Learning and Instruction (IJLI), 2025)
The purpose of this study is to assess and apply pedagogical principles in the development of academic websites at Universitas Tanjungpura's Fakultas Keguruan dan Ilmu Pendidikan (FKIP). The primary focus of this study is the application of the "mendorong kemandirian mahasiswa" principle in the context of student-centered learning. The method used is a kualitatif deskriptif with a focus on case studies, supported by observational, wawancara, and system analysis techniques based on the laporan pengembangan anjungan informationasi FKIP 2024. The study's findings indicate that an interactive, informative, and well-structured website design enables students to access and understand academic information independently without causing undue hardship to staff. The findings of this study indicate that the application of pedagogical principles in the design of academic information systems can enhance the use of technology as a teaching tool and a way to help students learn. Keywords: pedagogical principles, student-centered learning, information gathering, website design.